Toward a continuous learning educational model: insights from the experience of a Mexican private university - Camacho-Zuñiga, Claudia; Salas-Maxemín, Salvador; Valle-Arce, Ana Paula; Caratozzolo, Patricia; Chans, Guillermo M. (Frontiers in Education, 2025)
The rapidly evolving and technology-driven labor market underscores the need for continuous education and lifelong learning to ensure individuals remain adaptable and professionally relevant. It demands institutions that effectively bridge the gap between education and the workforce by promptly and pertinently modifying its programs and curricula, led by educators who are highly experts in specific skills and knowledge, as well as with pedagogical knowledge. In this address, robust educational models become essential. The TEC21 Educational Model (TEC21), introduced in 2019 by Tecnologico de Monterrey, addresses these challenges by fostering disciplinary and transversal competencies critical for success in the professional and personal spheres. This study explores two key research questions: (1) How do students in international experiences perceive the implementation of TEC21’s four components—inspiring professors, flexibility, challenge-based learning (CBL), and memorable university experiences—at their home and host universities? (2) How does TEC21 align with the European Commission’s Industry 4.0 Curriculum Guidelines? Semi-structured interviews were conducted with 13 Mexican engineering undergraduates during their international study experiences using a cross-sectional qualitative design. The findings reveal that Inspiring Professors—characterized by continuous pedagogical training and deep expertise in industry, consulting, or research—stood out as pivotal in preparing students for complex, real-world contexts. Flexibility and accessibility enable students to balance diverse priorities through hybrid learning environments, a critical feature for lifelong learners. For CBL, the model’s emphasis on interdisciplinary, real-world projects fosters employability, although collaboration with socio-formative organizations was less evident at host universities. The Memorable University Experience component highlighted the transformative nature of internationalization despite limited engagement with extracurricular activities and student organizations at host institutions. This study demonstrates TEC21’s alignment with the European Commission’s Industry 4.0 Curriculum Guidelines, addressing key pillars such as collaboration, quality assurance, and curriculum content. This model can inspire continuous education institutions to bridge the gap between education and industry demands. It equips graduates with adaptability, interdisciplinary collaboration skills, and global readiness, positioning TEC21 as a cornerstone for lifelong learning and sustainable societal advancement in the Artificial Intelligence era.